Small cell lung cancer: an overview of the targets - Bruna Nardy Valadares; Marco Antonio Stephano (Universidade de São Paulo, 2022)
Abstract Lung cancer is the leading cause of cancer deaths worldwide. Small cell lung cancer (SCLC) accounts for approximately 15% of all lung cancer cases. Despite a frequently good response to first-line treatment with chemotherapy and/or radiotherapy, early relapse occurs in the majority of patients and 5-year survival is only about 5%. This histological subtype of lung cancer is strongly associated with tobacco smoking. The behavior of SCLC is unique within solid tumors. Initially, it positively responds to chemotherapy or radiotherapy. However, at relapse, which occurs early in the majority of cases, the tumor is resistant to available therapy and eventually will cause the death of the patient. These results in an overall 5-year survival of approximately 5% for the entire population of patients diagnosed with SCLC. This dismal prognosis has not significantly changed in past years. There is an urgent need for discovery targets to select patients more prone to having a proper response to the treatment, avoiding to reduce their resistance and resulting the increase of overall and progression-free survivals.